Characterization of the nanoscratch, microstructure, and composition in hypoplastic amelogenesis imperfecta. (17th July 2015) - Qing, Ping; Li, Yue; Gao, Shanshan; Qiao, Mengting; Qian, Linmao; Yu, Haiyang
Hypoplastic amelogenesis imperfecta is a widespread hereditary disease that causes the loss of enamel. The purpose of this study was to investigate the nanoscratch resistance of hypoplastic amelogenesis imperfecta for providing a reference for restorative treatment. Four unerupted third molars from a patient diagnosed with hypoplastic amelogenesis imperfecta and seven unerupted third molars from normal individuals were compared. Atomic force microscopy and energy-dispersive X-ray spectroscopy were used to observe the microstructure and composition of the teeth (enamel and dentin). The nanoscratch tests of teeth (enamel and dentin) were investigated using a nanoscratch tester, scanning electron microscopy, and a stylus profilometer. The results indicated that hypoplastic amelogenesis imperfecta teeth had different microstructures compared to normal teeth. Hypoplastic amelogenesis imperfecta demonstrated a higher composition of organic substance. Meanwhile, the friction coefficient of hypoplastic amelogenesis imperfecta was higher than that of normal teeth, and inferior frictional resistance of hypoplastic amelogenesis imperfecta teeth was observed. The main damaging mechanisms observed in hypoplastic amelogenesis imperfecta under nanoscratch were the combination of delamination, debris, and cracks in enamel with delamination, debris, and plastic deformation in dentin. Our findings suggested that new dental restorative materials should be selected to match the mechanical properties of hypoplastic amelogenesis imperfecta.